Diagnóstico socioeconómico y perspectivas de internacionalización: Estudio de caso 14 empresas de la Región Brunca - Sáurez Ulloa, Max (2014)
The article analyzes the possibilities of internationalization that has 14 micro Brunca Region. This internal competitive business conditions and business environment that provides the environment where companies develop valued.The cantons of Buenos Aires, Coto Brus and Golfito present conditions of social vulnerability and socio-economic characteristics favor the productive activities that require little education is linked as agribusiness and trade. Economic activity in the area is linked to major agricultural export companies and many SMEs in the area of trade and services.The analysis of this group of micro and small businessmen / women who donot have much time after starting their small businesses, can have a followsocio-economic study to determine its potential and analyze their potential for sustainability and growth. The results are satisfactory to the extent that a very large entrepreneur will evidenced. Training needs are evident in the case of businesses that are related to the services sector.